CYTOTOXICITY OF THREE SOUTH AFRICAN MEDICINAL PLANTS USING THE CHANG LIVER CELL LINE - Otang, Wilfred Mbeng; Grierson, Donald Scott; Ndip, Roland Ndip (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Arctotis arctotoides, Gasteria bicolor and Pittosporum viridiflorum are commonly used in the Eastern Cape, South Africa by traditional healers for the treatment of opportunistic fungal infections in HIV/AIDS patients. Unfortunately, there is a dearth of published data regarding the toxicity of the selected plants, despite the fact that experimental screening of toxicity is crucial to guarantee the safety of the users. Therefore, it was decided to evaluate the cytotoxicity of the hexane and acetone extracts of the medicinal plants against the Chang Liver cell line using the in vitro MTT assay. Different concentrations of the extracts were added into 24-hour cultured cells and incubated for 72 hours under specific condition (37 °C, 5% CO2). Cell survival was evaluated using the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay. Depending on the dosage and duration of treatment, the cytotoxic effects of Gasteria bicolor and Pittosporum viridiflorum were considered relatively weak (but not entirely absent) and less of a toxicity risk. Arctotis arctotoides extracts were the most toxic both in terms of IC50 values as well as the steeper slope of the dose response curve. The IC50 values for the acetone and hexane extracts of this plant were 17.4 and 12.4 μg/ml respectively. These relatively low values raise concern for potential hepatotoxic effects and deserve further investigation or at least a warning to potential users.